Communication skills training - Orey, Maureen (ASTD trainer's workshop series., 2015)
Individuals, teams, and organizations are only as good as their ability to communicate effectively. This guide offers the crucial tools you'll need to help your workshop participants master the skills that drive performance. This first book in the ATD Workshop Series offers This volume incorporates technology in the delivery of half-, full-, and two-day workshops and offers design, delivery, facilitation, and evaluation advice that can be quickly and easily implemented. --